Characterization of the nutlet morpho-anatomical features of 12 Stachys taxa (Lamiaceae) from Turkey and its systematic practice - Karaismailoğlu, Mehmet Cengiz; Guner, Ozal; Akcicek, Ekrem; Karaismailoğlu, Mehmet Cengiz (Magnolia Press, 2022)
This study contains the nutlet morpho-anatomical characters of 12 taxa, 9 of which are endemic, belonging to subsection Multibracteolatae of section Fragilicaulis of the genus Stachys from Turkey in a systematical context with utilizing cluster and principal component analyses. Morphological characteristics such as the shape, color, size, surfaces and microstructures of the nutlets have been examined with using light and scanning electron microscopes. Anatomically, the structures and thicknesses of the pericarp have been investigated. The consequences have disclosed that the taxa are macro-morphologically different from each other in terms of shape, color, size, presence of wings and trichomes of nutlets. Nutlet sizes range from 2.23 mm to 3.43 mm in length, and from 1.25 mm to 2.22 mm in width. As, S. laetivirens and S. megalodonta subsp. megalodonta are of the largest nutlets, S. megalodonta subsp. mardinensis and S. mardinensis have the smallest nutlets. Unlike the other taxa examined, S. megalodonta subsp. mardinensis and S. baytopiorum bear wing on the nutlet. Also, S. megalodonta subsp. megalodonta is unique with non-glandular trichomes on nutlet among the examined taxa. Nutlet surface ornamentation is clustered into 6 types: reticulate, reticulate-areolate, scalariform, verrucate, alveolate and reticulate-foveate. The most common type is reticulate, while scalariform, alveolate and reticulate-foveate ornamentation types are noticed as taxon-specific. Anatomically, the structure and thickness of the pericarp and its parts are the significant characters that reveal inter-specific correlations among the examined taxa. A diagnostic key is offered for the recognition of the studied taxa based on the nutlet characters.
Keywords: Anatomy; Labiatae; Multibracteolatae; Nutlet; Sem; Turkey